Distribuição espacial da hanseníase em menores de 15 anos no Estado do Espírito Santo, entre 2010 e 2014 - Rodrigues, Taciana Gabrielle Pinheiro de Moura (2016)
Introduction: Known since Ancient History, Hansen’s disease still presents a challenge to Public Health. According to the Ministry of Health, the diagnosis of Hansen’s disease in people under 15 needs to prioritized, since cases in that age group can represent the individuals exposed, but still not diagnosed by the healthcare system. Therefore, an analysis was made of the spatial distribution of the detection coefficients of new cases of Hansen’s disease in people under 15 years old in the State of Espírito Santo. Methods: Descriptive, ecological study of the spatial distribution of Hansen’s disease in people under 15 in the state of Espírito Santo between 2010 and 2014. The information was collected at the Hansen’s disease database of the Health Secretariat of the State of Espírito Santo. The global and local Empirical Bayes method was applied in order to produce an estimate of the incidence of Hansen’s disease, smoothing out the effect of the fluctuation of the detection coefficients. Results: High incidence rates in people under 15 were found in the Northern region of the state. The corrected rates by the Ebest Global method produced significant changes in value: of the 42 municipalities with zero incidence, none remained with the adjusted number equals zero. Conclusion: The Hansen’s disease distribution in people under 15 years old took place in a heterogenic form among the municipalities, identifying possible high-risk sickening regions. The employment of the spatial analysis allows knowing the priority places to be controlled in order to guide health-care public policies, helping to plan the vigilance actions.